High‐definition blood flow imaging in the assessment of left ventricular function: Initial experience and comparison with contrast echocardiography. - Wu, Geru; Xie, Tianrong; Dimaano, Meneleo M.; Alghrouz, Mohammad I.; Ahmad, Masood (Echocardiography, 2019)
Objectives: The study aimed to assess the accuracy and reproducibility of the high‐definition blood flow imaging (HD‐Flow) in evaluation of left ventricular (LV) function by comparison with contrast echocardiography (Contrast). Background: Contrast improves endocardial border visualization and assists in precise assessment of LV function. HD‐Flow, a novel ultrasound technique that enhances blood flow discrimination in LV, could possibly be used for improving endocardial border definition without contrast. Methods: Eighty patients with technically limited transthoracic echocardiograms had HD‐Flow, and contrast performed sequentially. LV endocardial visualization, image acquisition time, wall motion, volumes, ejection fraction (EF), stroke volume (SV), and stroke volume index (SVI) were compared. Inter‐ and intra‐observer agreements were examined in a randomly selected subgroup. Results: Both HD‐Flow and contrast significantly improved the percentage of the well‐defined endocardial border segments (71% at baseline vs 94.1% by HD‐Flow vs 94.9% by contrast, X2 = 401, P < 0.001). The acquisition time for HD‐Flow was significantly less when compared to contrast (2.13 ± 1.18 minutes vs 10.96 ± 3.51 minutes, P < 0.001). LV end‐diastolic volume (EDV), end‐systolic volume (ESV), EF, SV, and SVI measured by the two methods correlated well (EDVr = 0.97, ESVr = 0.96, EFr = 0.90, SVr = 0.77, SVIr = 0.74, all P < 0.001). In comparison, HD‐Flow was neither significantly different in detecting LV wall motion abnormality nor in EF, SV, and SVI measurements, but slightly underestimated LV volumes. Conclusions: HD‐Flow imaging is feasible and user‐friendly in enhancing LV endocardial definition. This technique is useful in both qualitative and quantitative assessment of LV function.